Pengaruh Komisaris Independen, Kepemilikan Institusional, Kualitas Auditor, Volatilitas, Siklus Operasi, Keandalan Terhadap Persistensi Laba - Sulistiyo, Glenaydick Ezequiel; Indarto, Stefani Lily (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the effect of Independent Board of Commissioners, Institutional Ownership, Auditor Quality, Cash Flow Volatility, Operating Cycle, and Accrual Reliability on the earnings persistence of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. Using a quantitative approach with secondary data from financial statements and annual reports. The data analysis technique used in this study is multiple regression analysis technique with SPSS version 26 program. The results of the analysis show that the significance value of t for the Independent Board of Commissioners is 0.222> 0.05 with a beta coefficient value of -0.003, which means that the Independent Board of Commissioners has no effect on Earnings Persistence, the significance value of t for Institutional Ownership is 0.014 <0.05 with a beta coefficient value of +0.000, which means that Institutional Ownership has a positive effect on Earnings Persistence, the significance value of t for Auditor Quality is 0.020 <0.05 with a beta coefficient value of +0.012, which means that Auditor Quality has a positive effect on Earnings Persistence, the significance value of t for Cash Flow Volatility is 0.000 <0.05 with a beta coefficient value of +0.488, which means that Cash Flow Volatility has a positive effect on Earnings Persistence, the significance value of t for Operating Cycle is 0.019 < 0.05 with a beta coefficient of -0.000, meaning that the Operating Cycle has a negative effect on Earnings Persistence and the significance value of t for Accrual Reliability is 0.003 < 0.05 with a beta coefficient value of +0.008, meaning that Accrual Reliability has a positive effect on Earnings Persistence. The limitation of this study lies in its scope which only covers the manufacturing sector in Indonesia, so the results cannot necessarily be generalized to other sectors. This finding contributes to understanding the factors that influence earnings persistence and highlights the need for further research related to the effectiveness of supervision by the Independent Board of Commissioners in corporate governance of manufacturing companies in Indonesia.